Construction requirements of the water supply of Constantinople and Anastasian Wall - Snyder, James Riley (The University of Edinburgh, 2013)
With the end of Western Roman rule and the emergence of new polities in the medieval world, it has been assumed that the technology of mortar reverted to a weak and friable building material. However, this period brought about the implementation of large-scale construction projects that still remain as a testament to their high quality construction techniques and materials. In order to meet the needs of its growing populace, the infrastructure of the new capital city of Constantinople was bolstered by these projects, many rivaling the scale and intricacy of Imperial Rome. A prime example of this is the extensive channel networks of the fourth and fifth centuries, built in the hinterland of Constantinople to supply fresh water from springs hundreds of kilometres away. In addition, the sixth century Long Wall of Thrace was built from the Black Sea to the Sea of Marmara as a first line of defense against increased aggression. This project examines the tradition of monumental construction in the Late Antique and early Byzantine world through laboratory analysis of mortars and valuations of the structural makeup of the Water Supply of Constantinople and Anastasian Wall. By investigating the material technology, scale, and labour requirements of these systems, a better understanding can be gained of two of the largest building project of the early medieval period.
Keywords: construction; materials; aqueduct; Anastasian Wall; late antiquity; Constantinople; building; manpower; petrography; mortar